Effectiveness of High-Intensity Physical Exercise (HIIT) through Poundfit Exercise on Cognitive Function in Young Adults with A Sedentary Lifestyle - Mutiara Alya Zahra; Upik Rahmi; Slamet Rohaedi; Ridha Wahdini (Indonesian Journal of Global Health Research, 2026)
Technological developments and lifestyle changes following the COVID-19 pandemic have increased the prevalence of sedentary behavior in young adults, potentially negatively impacting cognitive function. Physical activity interventions, particularly High-Intensity Interval Training (HIIT), are known to have benefits for brain health. Pound Fit is a form of HIIT that combines high-intensity exercise, rhythmic music, and motor coordination, but empirical evidence regarding its effects on cognitive function in sedentary young adults is still limited. This study aims to analyze the effectiveness of HIIT through Pound Fit on cognitive function in young adults with a sedentary lifestyle. This study used a Randomized Controlled Trial (RCT) design with a quantitative approach. The MoCA-Ina has been reported to have good construct validity and high reliability with a Cronbach's Alpha value >0.70, making it considered reliable for measuring cognitive function in the Indonesian population. A total of 40 female Nursing students with a sedentary lifestyle were recruited and randomly divided into an intervention group (n=20) and a control group (n=20). The intervention group participated in a HIIT-based Pound Fit exercise program for four weeks (3 times/week, ±45 minutes/session), while the control group carried out their usual activities. Cognitive function was measured using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) before and after the intervention. Data analysis was performed using a Paired Samples t-test and an Independent Samples t-test . The results of the paired samples t-test showed a significant increase in cognitive function in the intervention group after Pound Fit exercise (p < 0.001). The independent samples t-test also showed a significant difference in cognitive function scores between the intervention group and the control group in the posttest measurement (p < 0.001). All data met the assumptions of normality and homogeneity. HIIT training through Pound Fit exercise has been proven effective in improving cognitive function in young adults with a sedentary lifestyle. This intervention has the potential to be an applicable promotive and preventive strategy in nursing and public health practice to support the cognitive health of young adults.